2016
DOI: 10.1186/s13756-016-0156-x
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of ESBL/AmpC-producing or ciprofloxacin non-susceptible Escherichia coli and Klebsiella spp. in healthy people in Norway

Abstract: BackgroundAsymptomatic carriage has been recognised as an important risk factor for infection caused by antibiotic resistant bacteria. A 14% global prevalence of Extended-Spectrum Beta-lactamase (ESBL) carriage was recently reported, but large intra-and interregional variations were observed. We investigated the faecal carriage rates of ESBL-, AmpC-producing and ciprofloxacin non-susceptible Escherichia coli and Klebsiella spp. in healthy Norwegians.MethodsRectal samples were obtained from 284 volunteers, toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 33 publications
8
27
0
Order By: Relevance
“…Risk factors associated with the carriage of AmpC-positive Enterobacteriaceae could not be identified, probably due to the small number of carriage rate. However, our results suggested that the AmpC-producers have spread beyond hospital settings in Thailand, as seen in other studies elsewhere [7,9] . In addition, the co-existence of two ß-lactamase genes in a single isolate were found in 6.5% of isolates (19/291) ( Table 2).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Risk factors associated with the carriage of AmpC-positive Enterobacteriaceae could not be identified, probably due to the small number of carriage rate. However, our results suggested that the AmpC-producers have spread beyond hospital settings in Thailand, as seen in other studies elsewhere [7,9] . In addition, the co-existence of two ß-lactamase genes in a single isolate were found in 6.5% of isolates (19/291) ( Table 2).…”
Section: Discussionsupporting
confidence: 80%
“…Several reports on the intestinal carriage of ESBL + E in community settings have been documented. Studies in the European countries such as the Netherlands and Norway revealed a small number (<10%) of ESBL + E in healthy subjects [7,9] . The relatively low carriage rates of ESBL + E among healthy populations were reported from Asia, including Japan [22] and Korea [23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The frequency of ESBL-K. pneumoniae in our study was higher in lung cancer patients than in the healthy population. 28 The most common determinants were the bla CTX-M , bla SHV and bla TEM genes in two dominant pulsotypes, which have been reported to be the most frequent ESBLs in K. pneumoniae isolates. 26 Epidemiological studies suggest that the increasingly widespread occurrence of CRKP has become a major public health crisis.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, our results indicate that working as a veterinarian does not increase carriage rates of ESBL/pAmpC‐PE. Numbers from other Nordic countries with low occurrence vary from 3.2% to 4.9% (Egervärn et al, ; Ulstad et al, ). Our findings are in line with results of a study conducted in Dutch slaughterhouses which found an overall prevalence equalling that of the general population (Dohmen et al, ).…”
Section: Discussionmentioning
confidence: 99%